EFL teachers' evaluation and adaptation of the listening tasks in the piloted tieng Anh 10: A case of high schools in Kien Giang province. - Phan, Thị Phương Lan (Trường Đại học Cần Thơ, 2019)
The study aims to investigate the EFL teachers’ evaluation of the listening tasks in the piloted Tieng anh 10 and identify how they adapt these tasks in their process of teaching.